Antioxidant and anti-inflammatory activities of fractions from Jatropha curcas Linn. root extract and attenuation of pro-inflammatory mediators in RAW 264.7 cells - Osman, Shahirah Atiqah (2017)
Jatropha curcas Linn. plant belongs to the Euphorbiaceae family. This plant has been widely used in traditional medicine to treat injuries, fever, mouth infections, jaundice, guinea worm sores, and joint rheumatism. Among the different parts of the plant, the root has been widely used in ethno-medicine. However, extracts prepared from the roots could be variable in terms of efficacy and safety. The method of extraction and solvents used play a crucial role in determining the biological activities. It was hypothesized that liquid-liquid fractionation process could extract metabolites from J. curcas root which possessed antioxidant and anti-inflammatory activities without cytotoxic effect in the cell lines used. Therefore, the main objective of the present study was to investigate the biological activity and cytotoxicity of different solvents extract from J. curcas root. The metabolites were partitioned by using different solvents with different polarities. The phenolic and flavonoid contents of each solvent fraction were analyzed colorimetrically, and each fraction was evaluated for antioxidant and anti-inflammatory activities in macrophage RAW 264.7 cell lines. The nature of compounds present in each fraction was analysed by Liquid Chromatography Mass Spectrometry (LCMS). The active fraction with anti-inflammatory activity and low cytotoxicity was used to study the expression of pro-inflammatory genes by qPCR. The peripheral roots were collected from three J. curcas plants approximately 4 to 5 years old and subjected to 80% methanolic extraction for the preparation of dried root extracts. Then, the methanolic extract was used in the liquid-liquid fractionation technique with five different solvents (hexane, chloroform, ethyl acetate, n-butanol, and aqueous). This was followed by determining the antioxidant activity of different fractions in vitro using 1,1-Diphenyl-2-Picrylhydrazyl (DPPH) free radical scavenging, ferric-reducing antioxidant power (FRAP) assay and scavenging of ABTS (2,2′-azinobis[3-ethylbenzothiazoline-6-sulphonate])-nitrogen-centred radical cation (ABTS+) assay. The results showed that ethyl acetate and n-butanol fractions of the three root samples possessed high antioxidant activity with the highest total phenolic (36.74 ± 0.046 GAE μg /g DW and 33.12 ± 0.006 GAE μg /g DW) and total flavonoid content (11.76 ± 0.015 GAE μg /g DW and 10.11 ± 0.009 GAE μg /g DW). The anti-inflammatory activity of all five fractions was evaluated using murine macrophage RAW 264.7 cell line by determining the percentage of nitric oxide (NO) production by Griess reaction. The cytotoxicity activity of each fraction was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction method using murine macrophage RAW 264.7 cell line. The results showed that NO inhibition by n-butanol fraction at the concentration of 100 μg/mL in macrophage RAW 264.7 cells was 86% and cell viability was 105%, comparable to curcumin treated cells. The LCMS analysis showed that ethyl acetate contained epigenin and kaempferol glucoside isomer, which were categorised under flavone and phenolics that possessed antioxidant and anti-inflammatory properties. While n-butanol fraction contained high amount of coumaric acid and p-coumaroylquinic acid that could be involved in anti-inflammatory activity. The n-butanol fraction was evaluated using qPCR technique to study the expression of genes (iNOS, TNF-α, IL-6, and IL-1β genes) involved in inflammatory activity of induced lipopolysaccharide (LPS) and interferon-gamma (IFN-γ) RAW 264.7 cells, where cells treated with curcumin was used as positive control and normalized by expression of housekeeping gene transcript (G3DPH). The results showed that n-butanol fraction at 100 μg/mL, significantly (P<0.05) reduced the expression of iNOS, TNF-α, IL-6, and IL-1β genes. Hence, the anti-inflammatory effect was due to the down-regulation of the pro-inflammatory mediators. The present study showed that liquid-liquid fractionation was successful in partitioning the metabolites present in the J. curcas root methanolic extract, where n-butanol fraction was observed to be the most active fraction among other fractions. This fraction contained metabolites which possessed strong antioxidant and anti-inflammatory properties with low cytotoxicity activity and the ability to down-regulated the expression of all four pro-inflammatory genes evaluation.